Early Memories of Individuals on the Autism Spectrum Assessed Using Online Self-Reports - Zamoscik, Vera; Mier, Daniela; Schmidt, Stephanie N. L.; Kirsch, Peter (Frontiers in Psychiatry, 2016)
“When I was one and a half years old, I was on a ferry lying on red seats” – while several autobiographical accounts by people with autism reveal vivid memories of early childhood, the vast amount of experimental investigations found deficits in personal autobiographic memory in autism. To assess this contradiction empirically, we implemented an online questionnaire on early childhood events to compare people on the autism spectrum (AS) and non-autistic people with respect to their earliest autobiographical episodic memories and the earliest semantic know event as told by another person. Results indicate that people on the AS do not differ from non-autistic people in the age of their earliest know events but remember events from an earlier age in childhood and with more sensory details, contradicting the assumption of an overall deficit in personal episodic memory in autism. Furthermore, our results emphasize the supporting influence of language for memory formation and give evidence for an important role of sensory features in memories of people on the AS.